PENGARUH ELEMEN-ELEMEN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN MOBIL TOYOTA KIJANG INNOVA PADA PT. NASMOCO PEMUDA SEMARANG - Euis Daeng Jintu; Rodhiyah Rodhiyah; Andi Wijayanto (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to determine the effect of the brand equity elements to the purchasing decisions of Toyota Kijang Innova on PT. Nasmoco Pemuda Semarang. The type of research used is explanatory research with 95 respondents taken using a purposive sampling technique. The analysis technique used is linier regression with SPSS for windows. The results showed that the brand awareness have a positive effect on purchasing decisions, brand association have a positive effect on purchasing decision, perceived quality have a positive effect on purchasing decisions, and Brand loyalty have a positive effect on purchasing decisions. Brand awareness, brand association, perceived quality, and brand loyalty are jointly contributing positively towards purchasing decisions. Advised to PT. Nasmoco Pemuda Semarang needs to make improvements in marketing strategy to attract more customers in the future, so that it can be more exciting to the consumers. Wear jingle song or attractive slogans to be remembered by the consumers, Making a good marketing communications to get new customers, also to decide the price appropriated to the specifications and quality products offered to create a purchasing decisions.